KEBIJAKAN PENANGGULANGAN TAWURAN ANTAR REMAJA DI WILAYAH JAKARTA BARAT - Yeremia Aprilio; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2022)
Brawl is a fight between groups using supporting tools in the form of sharp weapons, stones andso on. Brawls between students in the West Jakarta area are still common. The factor of theexistence of brawls between teenagers is a very bad friendship environment and also from familyfactors that do not always monitor or see the growth and development of their children from thelevel of children to the level of adults. The impact of the brawl is the destruction of public facilitieswhich can disturb the community and cause casualties and injuries. The National Police of theRepublic of Indonesia is one of the law enforcement of icers in Indonesia who plays an active rolein tackling and taking action against the perpetrators of brawls. One of the goals of the police is tomake people feel safe and comfortable to carry out their activities. The perpetrators of suchbrawls can be subject to criminal sanctions under Article 170 of the Criminal Code which reads